An in situ SAXS investigation of the formation of silver nanoparticles and bimetallic silver–gold nanoparticles in controlled wet-chemical reduction synthesis. Issue 1 (25th November 2019) - Garcia, Paulo R. A. F.; Prymak, Oleg; Grasmik, Viktoria; Pappert, Kevin; Wlysses, Wagner; Otubo, Larissa; Epple, Matthias; Oliveira, Cristiano L. P.
Abstract : In situ investigation of metallic nanoparticle synthesis with an online monitoring of the system by SAXS. Determination of structural parameters and growth processes. Ag-NP synthesis presented a bimodal system with the presence of small particles (∼3 nm). Abstract : We present a study on the formation of silver (Ag) and bimetallic silver–gold (AgAu) nanoparticles monitored by in situ SAXS as well as by ex situ TEM, XRD and UV-vis analysis in a flow reactor at controlled reaction temperature. The formation mechanism of the nanoparticles is derived from the structural parameters obtained from the experimental data. The evolution of the average particle size of pure and alloyed nanoparticles shows that the particle growth occurs initially by a coalescence mechanism. The later growth of pure silver nanoparticles is well described by Ostwald ripening and for the alloyed nanoparticles by a process with a significantly slower growth rate. Additionally, the SAXS data of pure silver nanoparticles revealed two major populations of nanoparticles, the first one with a continuous crystal growth to a saturation plateau, and the second one probably with a continuous emergence of small new crystals. The particle sizes obtained by SAXS agree well with the results from transmission electron microscopy and X-ray diffraction. The present study demonstrates the capability of an in situ investigation of synthesis processes using a laboratory based SAXS instrument. Online monitoring of the synthesis permitted a detailed investigation of the structural evolution of the system.